Cardiovascular Magnetic Resonance Imaging in Congenital Heart Disease as an Alternative to Diagnostic Invasive Cardiac Catheterization: A Single Center Experience. (21st January 2013) - Heathfield, Emily; Hussain, Tarique; Qureshi, Shakeel; Valverde, Israel; Witter, Thomas; Douiri, Abdel; Bell, Aaron; Beerbaum, Philipp; Razavi, Reza; Greil, Gerald F.
Abstract Objective The study aims to assess whether the increasing use of cardiovascular magnetic resonance imaging in place of diagnostic cardiac catheterization in the management of pediatric patients with congenital heart disease has had an impact on pediatric cardiac care. Design Retrospective analysis of data was used. Setting The study was performed at the Evelina Children's Hospital Cardiology Department. Patients. Elective diagnostic cardiac catheterization or magnetic resonance imaging (MRI) from 2005–2010 are included (n = 896). Outcome Measures Indication, length of stay, and incidence of complications were recorded. In cases used to plan surgery, 30‐day survival following the procedure was recorded. Surgical outcomes were compared between the two groups. Surgical outcomes planned using MRI were compared with national outcomes from Congenital Cardiac Audit Database. Results For catheterizations (50 patients, [31 male, median age 3 years, interquartile range 1 to 12]), median hospital stay was 1 day (interquartile range 0 to 3), and complications occurred in 11 (22%). Median hospital stay for MRI (846 patients [517 male, median age 3 years, interquartile range 0 to 9]) was significantly shorter: 0 days (interquartile range 0 to 1, P <.001), with fewer complications (16 [1.9%], P <.0001). Twenty‐four catheter and 283 MRI patients underwent surgery within 18 months. One catheter patient (2.0%) and four MRI patients (1.4%) died within 30 days (P =.48). Conclusion Replacing catheterization with cardiovascular magnetic resonance imaging has resulted in reduced rates of complication and shorter hospital stays without a significant impact on surgical outcome.